2019
DOI: 10.2147/ijn.s189888
|View full text |Cite
|
Sign up to set email alerts
|

<p>Distribution of SiO<sub>2</sub>&nbsp;nanoparticles&nbsp;in 3D liver microtissues</p>

Abstract: Introduction: Nanoparticles (NPs) are used in numerous products in technical fields and biomedicine; their potential adverse effects have to be considered in order to achieve safe applications. Besides their distribution in tissues, organs, and cellular localization, their impact and penetration during the process of tissue formation occurring in vivo during liver regeneration are critical steps for establishment of safe nanomaterials. Materials and methods: In this study, 3D cell culture of human hepatocarcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…Fleddermann et al found that SiO 2 -NPs were distributed through the whole HepG2 spheroid when the NPs were mixed with cells before spheroid formation. However, when exposing the already formed spheroids for 24 h, NPs were seen only to a depth of 20 µm [26]. Cell types, cell densities, physicochemical characteristics of the NPs (including size distribution) and ion release may influence the penetration inside the spheroid [73][74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fleddermann et al found that SiO 2 -NPs were distributed through the whole HepG2 spheroid when the NPs were mixed with cells before spheroid formation. However, when exposing the already formed spheroids for 24 h, NPs were seen only to a depth of 20 µm [26]. Cell types, cell densities, physicochemical characteristics of the NPs (including size distribution) and ion release may influence the penetration inside the spheroid [73][74][75][76][77].…”
Section: Discussionmentioning
confidence: 99%
“…This increases the cell-to-cell contacts and intercellular communication [22] and changes the protein expression and metabolic status of the cells [21][22][23]. HepG2 cells in 3D cultures show upregulation of genes involved in liver-specific xenobiotic and lipid metabolism, whereas genes related to the extracellular matrix, cytoskeleton and cell adhesion have higher expression in 2D cultures [22,24].The use of spheroids as 3D cultures in hepatotoxicity assessment is an increasing field of interest, and HepG2 spheroids, prepared with and without using scaffolds, have been applied for toxicity experiments with both NPs [6,25,26] and chemicals [27,28]. However, the differences in toxic responses between cells cultured in 2D and 3D are not yet clear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FDA was used to mark the live cells; FDA is taken up by the cells, cleaved to fluorescein by esterases which is impermeable to the cell membranes and hence stays within the cells. PI, on the other hand, is impermeable to the cell membranes and passes through the disintegrated membrane of dying cells, thereby probing dead cells (Fleddermann et al, ). Similar to resazurin reduction and LDH release, more PI stained (red), that is, dead cells were visible in the N0.5 group as compared to other scaffolds wherein FDA stained (green), that is, viable cells are visible (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…rapid proliferation at the surface and slow metabolism -or necrosis -in the center of spheroids 25 . The majority of studies of NP distributions in tumor spheroids use tumor spheroid fixation [26][27][28][29][30][31][32][33][34] , often in combination with histological sectioning 7,[35][36][37][38] . Nevertheless, there are also reports of NP penetration in live tumor spheroids using confocal-scanning microscopy [39][40][41][42][43][44][45][46][47][48][49] .…”
Section: Introductionmentioning
confidence: 99%